2019
DOI: 10.1515/erj-2018-0228
|View full text |Cite
|
Sign up to set email alerts
|

The Entrepreneurial Ecosystem: Actors and Performance in Different Stages of Evolution of Academic Spinoffs

Abstract: The importance of entrepreneurial ecosystems is accentuated in the academic entrepreneurship context since academic spinoffs (ASOs) must rely on actors from the ecosystem to access resources they lack in order to improve their performance. This study analyzes the impact that actors from social and institutional (university and nonuniversity) contexts in the entrepreneurial ecosystem have on ASO performance in the stage of creation and initial development and in the stage of consolidation. From a sample of 118 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The relevance of TTOs in the development of social innovation in ASOs differs from that of other organizations that fall outside the university context and therefore justifies the need to analyze the influence of the entrepreneurial ecosystem on the development of social innovation by ASOs. In addition, the study by Franco-Leal et al [20] indicated that TTOs are irrelevant for the economic performance of ASOs. This means that according to the ecosystem theory, the contexts of the entrepreneurial ecosystem affect the results of the companies in different ways, and hence, depending on the type of result or innovation developed by the firm, companies need to rely on different contexts of the entrepreneurial ecosystem [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The relevance of TTOs in the development of social innovation in ASOs differs from that of other organizations that fall outside the university context and therefore justifies the need to analyze the influence of the entrepreneurial ecosystem on the development of social innovation by ASOs. In addition, the study by Franco-Leal et al [20] indicated that TTOs are irrelevant for the economic performance of ASOs. This means that according to the ecosystem theory, the contexts of the entrepreneurial ecosystem affect the results of the companies in different ways, and hence, depending on the type of result or innovation developed by the firm, companies need to rely on different contexts of the entrepreneurial ecosystem [21].…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the key actors of the social and institutional contexts of the entrepreneurial ecosystem of ASOs, an extensive literature review was carried out, which revealed that the social context comprises relationships with national and international customers, suppliers, competitors, and VCs. The institutional context is composed of relationships with national and international government institutions, TTOs, incubators, other academics, chairs of entrepreneurs, and research centers [20,94,95]. By focusing on Mitchell [96] and Smith et al [97], the frequency of contact was employed to measure the interactions of ASOs with each agent.…”
Section: Methodological Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Along these same lines, Laurell et al (2017) highlight that not only are international relationships key to the internationalization process, but local networks are also essential, such as with universities and hospitals. Laurell et al (2013), Mikhailova andOlsen (2016), andFranco-Leal et al (2020) distinguish between academic, institutional, and social business relationship networks. Others, such as Coviello and Munro (1995), Rasmussan et al (2001), Shirokova and McDougall-Covin (2012), Laurell et al (2017), andSekliuckiene (2017), distinguish between formal (business-related) relationships and informal or social (family and friends) relationships.…”
Section: The Impact Of International Social Capital In the Internatio...mentioning
confidence: 99%